Stadt der Commonisten Neue urbane Räume des Do it yourself - Baier, Andrea (Urban Studies, 2013)
It's hard to miss: a new generation of do-it-yourself activists are using the post-Fordist city as a laboratory for social, political, environmental and aesthetic experimentation. Whether in the community garden or in the FabLab, whether in open workshops or at exchange events - everywhere the protagonists question the relationship between consumption and production, problematizing the commodity character of things and the knowledge they contain. This sophisticated illustrated book combines visual expeditions through the new urban spaces of DIY with stimulating time diagnoses. The contributions illustrate that the young urbanites do not rely on opposition but follow the need for "true democracy" by creating (atmo-) spheres of sharing and exchange. They practice collaborative consumption and play public space in the manner of the Commonists.